2016
DOI: 10.3389/fpubh.2016.00183
|View full text |Cite
|
Sign up to set email alerts
|

The Amagugu Intervention: A Conceptual Framework for Increasing HIV Disclosure and Parent-Led Communication about Health among HIV-Infected Parents with HIV-Uninfected Primary School-Aged Children

Abstract: Advances in access to HIV prevention and treatment have reduced vertical transmission of HIV, with most children born to HIV-infected parents being HIV-uninfected themselves. A major challenge that HIV-infected parents face is disclosure of their HIV status to their predominantly HIV-uninfected children. Their children enter middle childhood and early adolescence facing many challenges associated with parental illness and hospitalization, often exacerbated by stigma and a lack of access to health education and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 100 publications
0
27
0
Order By: Relevance
“…The content and intervention approach (Rochat et al., 2013), and the conceptual framework (Rochat et al., 2016), have been described elsewhere and are summarised in Supplementary Fig. S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content and intervention approach (Rochat et al., 2013), and the conceptual framework (Rochat et al., 2016), have been described elsewhere and are summarised in Supplementary Fig. S1.…”
Section: Methodsmentioning
confidence: 99%
“…The conceptual framework of the intervention is described in open access format elsewhere (Rochat et al., 2016) and includes a focus on increasing parent-child communication about HIV (generally, and through parental HIV disclosure) and assisting mothers to prepare for periods of illness. Mothers were encouraged to make either full (using the words ‘HIV’) or partial (using the word ‘virus’) disclosures (Qiao et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…4 While parents often avoid disclosure about HIV in an effort to protect children, 6,16 by primary school-age children are likely to be aware of parental HIV, particularly in epidemic areas. 12,16,19 Rates of disclosure in the Amagugu intervention were higher than those recorded in other research across the globe, including in Africa: Uganda (50%); Asia: Thailand (35%); North America: Canada (31%) and Europe (11%). Likewise, participants were willing to disclose to children at younger ages than has generally evidenced in LMIC literature.…”
Section: Discussionmentioning
confidence: 74%
“…24,25 The primary and secondary outcomes of this trial suggest that without the benefit of an intervention which actively encourages parents to deal with communication about HIV, health education and care planning, the rates of these remain low, which is concerning since the absence of these are known to confer risks. 5,19 We found that enhanced standard of care mothers were more likely to disclose to girls than boys, 6,7 possibly linked to expectations that girls will assist with caregiving during illness.…”
Section: Discussionmentioning
confidence: 81%
“…Adherence to ART, 24 support for breastfeeding, 55 such as that delivered by lay counsellors VTS, 35 and providing child stimulation, such as is provided by lay professionals in the WHO Child Care for Development, may be particularly suited to the early years of life. 56 In later years, mothers may face challenges related to periods of illness often coinciding with middle and later childhood where support for parent-child communication about HIV and HIV disclosure may then become particularly salient, 13,57 likewise successful interventions have been documented using lay counsellor home visiting models. 19,58 We show, for the first time in a Southern African population of parents of primary school-aged children, that parenting stress (above the clinical threshold) rather than depression or anxiety, contributes most to psychological distress in all mothers.…”
Section: Discussionmentioning
confidence: 99%